Characteristics of Mango Kernel Fats Extracted from 11 China‐Specific Varieties and Their Typically Fractionated Fractions. (2nd June 2016) - Jin, Jun; Warda, Pembe; Mu, Hongyan; Zhang, Youfeng; Jie, Liang; Mao, Jiahui; Xie, Dan; Huang, Jianhua; Jin, Qingzhe; Wang, Xingguo
Abstract: 11 China‐specific mango varieties, i.e., Tainong, Xiangya, Okrong, Keitt, Chiin Hwang, Guifei, Yuexi, Biantao, Guixiang, Zihua and Guire, were selected from South China, and the kernels were separated from pulps and then dried to extract mango kernel fats (MKF). 5.65–11.14 % of the fats could be obtained from dried kernels using hexane extraction, and their iodine values, slip melting points, triacylglycerols, sn ‐2 fatty acids and micronutrients were analyzed. MKF were comprised predominantly of triacylglycerols reaching 85.09–92.72, and 78.28–84.37 % of oleic at the sn ‐2 position. 29.99–55.44 % of SOS, 11.17–23.34 % of SOO and 13.10–19.79 % of POS occupied the main percentages of triacylglycerols, indicating MKF have diversified application after fractionation. Certain variety characterized as moderate values mentioned above, therefore, was selected and then fractionated by two‐stage processes to produce typical MKF fractions. The stearin (Fraction‐II) fractionated from the first solid fraction (Fraction‐I) with 68.09 % of SOS and 15.43 % of POS was more suitable as cocoa butter improver, while the olein (Fraction‐III) produced from the first liquid fraction was rich in SOO (45.59 %), POO (11.37 %) and OOO (11.14 %), which are considered as ideal cooking oil or frying fat ingredients. In addition, high amounts of micronutrients, including sterol, tocopherol and squalene, were also found in MKF ranged from 3837 to 7085, 81 to 916, and 164 to 941 mg/kg among different varieties, respectively. In particular, squalene levels were higher compared with most of other vegetable oils.